Molecular Response of the Acidophilic Iron Oxidizer “Ferrovum” Sp. ja12 to the Exposure to Elevated Concentrations of Ferrous Iron - Levican-Jaque, G (Trans Tech Publications Ltd, 2017)
The response to elevated ferrous iron concentrations was investigated in the acidophilic iron oxidizer “Ferrovum” sp. JA12 at transcriptome level. Detoxification of reactive oxygen species appears to be the most important strategy to cope with oxidative stress. The proposed iron oxidation model in “Ferrovum” spp. was supported by the transcriptome data of “Ferrovum” sp. JA12. Several gene candidates of the iron oxidation model are organized in a gene cluster conserved in iron oxidizing betaproteobacteria and zetaproteobacteria possibly indicating a common origin of iron oxidation. © 2017 Trans Tech Publications, Switzerland.